2013
DOI: 10.1007/s00268-013-2401-2
|View full text |Cite
|
Sign up to set email alerts
|

ALPPS for Patients with Colorectal Liver Metastases: Effective Liver Hypertrophy, but Early Tumor Recurrence

Abstract: The patient group operable only through ALPPS is at high risk for recurrence and early tumor progression. Still, this new method is the only chance for an oncological treatment strategy including a surgical approach and possibly better outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
97
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(112 citation statements)
references
References 17 publications
5
97
1
5
Order By: Relevance
“…However, clinical as well as experimental data are controversial and need further investigation. While some authors described an earlier tumor recurrence in admittedly very small series, the meta-analysis by Moris et al [48] showed similar tumor recurrence rates for TSH and ALPPS [50]. However, since there is a great variability in indications and patient selection for TSH and ALPPS from center to center, it is most likely that comparability of data is limited.…”
mentioning
confidence: 99%
“…However, clinical as well as experimental data are controversial and need further investigation. While some authors described an earlier tumor recurrence in admittedly very small series, the meta-analysis by Moris et al [48] showed similar tumor recurrence rates for TSH and ALPPS [50]. However, since there is a great variability in indications and patient selection for TSH and ALPPS from center to center, it is most likely that comparability of data is limited.…”
mentioning
confidence: 99%
“…8,9 Three methods to enlarge FLR are possible in this situation before ERH: (1) surgical right-sided portal vein ligation (PVL), 10,11 (2) portal vein embolization (PVE) as an interventional approach used by various centres [12][13][14] and (3) the surgical approach of "associating liver partition with PVL for staged hepatectomy". [15][16][17] However, as hypertrophy following PVE is necessary but highly variable, we retrospectively analyzed data from our patient cohort for differences in those with good hypertrophy (increase to .25% of the sFLR) and those with a less beneficial increase in size of sFLR.…”
Section: Introductionmentioning
confidence: 99%
“…metastases. In fact, as shown by the ALPPS registry data, colorectal liver metastases currently represent the primary indication for ‘in-situ split' liver resection/ALPPS in our center and worldwide [14,15,19,20,21,22]. …”
Section: Discussionmentioning
confidence: 99%